2019
DOI: 10.1007/s00394-019-02108-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of protein and essential amino acid supplementation on muscle strength and performance in patients with chronic heart failure: a systematic review

Abstract: Purpose Critically low skeletal muscle mass and strength, observed in 20% of people with chronic heart failure (CHF), reduces functional capacity, quality of life (QoL) and survival. Protein and essential amino acid (EAA) supplementation could be a viable treatment strategy to prevent declines in muscle strength and performance, and subsequently improve QoL and survival. This systematic review (PROSPERO: CRD42018103649) aimed to assess the effect of dietary protein and/or EAA supplementation on muscle strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 58 publications
0
21
0
1
Order By: Relevance
“…Amino acids are either ingested or endogenously synthesized in the human body and play important physiological roles as basic metabolites and metabolic regulators. Amino acids are key substrates required for mitochondrial metabolism and are usually elevated in HF groups [ 32 , 33 ]. Glutamic acid, an amino acid, plays an important role in the creation of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acids are either ingested or endogenously synthesized in the human body and play important physiological roles as basic metabolites and metabolic regulators. Amino acids are key substrates required for mitochondrial metabolism and are usually elevated in HF groups [ 32 , 33 ]. Glutamic acid, an amino acid, plays an important role in the creation of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It was also noted that the randomised trials included in this review had a high risk of bias, and thus, more evidence is needed to elucidate the benefits of protein supplementation in heart failure patients. 62 In older adults with type 2 diabetes, previous research has shown they often experience accelerated loss in SMM and strength in comparison with age-matched, normoglycaemic controls, 63 which is related, in part, to insulin resistance impairing muscle protein synthesis. 64 Given that skeletal muscle is the largest mass of insulin-sensitive tissue and the key storage site for glucose, preserving muscle mass is important for this clinical population.…”
Section: Supplementation In Patients With Comorbiditiesmentioning
confidence: 99%
“…60 Another study supplementing 17 heart failure patients with l-alanyl-l-glutamine (8 g/day) and polyunsaturated fatty acid (6.5 g/day) for 3 months reported gains in lean body mass (+1.7 ± 0.3 kg) and quality of life (+13 ± 11 points) when compared to an isocaloric placebo, but no changes in hand grip or leg strength were observed. 61 A recent systematic review of 167 heart failure patients (>18 years) suggests that chronic (>4 weeks) protein and/or EAA supplementation may improve lean body mass and quality of life; 62 however, no effect on muscle strength was reported. It was also noted that the randomised trials included in this review had a high risk of bias, and thus, more evidence is needed to elucidate the benefits of protein supplementation in heart failure patients.…”
Section: Supplementation In Patients With Comorbiditiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nichols et al [ 19 ] performed a systematic review of the effect of amino acid supplementation in heart failure. They demonstrated that essential amino acid supplementation could improve important outcome measures related to sarcopenia.…”
Section: Beneficial Effect Of Bcaa In Patients With Heart Failurementioning
confidence: 99%